Study on the Macromesoscopic Yield Criterion of Concrete Material - Xia XiaoZhou; Zhang Qing; Jiang Qun; Xiao JianQiang (Advances in Condensed Matter Physics)
In mesoscopy, the concrete material is a kind of composite consisting of mortar matrix, aggregate, and the interface between them. And the shape of aggregate is assumed to be spherical and the mortar matrix is supposed to satisfy the Drucker-Prager yield criterion. The energy density support function is introduced to reflect the yield surface of mortar matrix. In order to solve the nonderivability on the yield boundary, the function approximation series has been constructed to substitute for the energy density support function. Finally, based on the function series, a macromesoscopic yield criterion of concrete material has been derived by the nonlinear homogenized technique. Through the macromesoscopic yield criterion established, the influence law of the bonding status of interface and the fraction of aggregate on the macrofriction coefficient is explored.